2012
DOI: 10.1590/s0103-05822012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do uso de chupeta em lactentes amamentados e não amamentados atendidos em um hospital universitário

Abstract: Prevalence of pacifier among breastfed and not breastfed infants attending a university hospital ABSTRACTObjective: To evaluate the prevalence of pacifier use in relation to breastfeeding, to find out the reasons why mothers planned or not to introduce this habit and the arguments for changing their minds about the pacifier used.Methods: Cross sectional study comprising 642 motherinfant pairs (0-12months) at a University Hospital, in Campinas, São Paulo, Brazil. The mother was questioned about her original int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 27 However, there is no consensus on the adverse effects of pacifiers and many results are controversial in the literature. 6 , 14 , 15 , 16 Boccolini et al 16 pointed out that the use of pacifiers was the aspect most strongly associated with the early interruption of exclusive BF in the studies evaluated. Its use may imply a decrease in the frequency of sucking, resulting in less stimulation of the nipple-areolar complex and consequent reduction in the production of breast milk.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 27 However, there is no consensus on the adverse effects of pacifiers and many results are controversial in the literature. 6 , 14 , 15 , 16 Boccolini et al 16 pointed out that the use of pacifiers was the aspect most strongly associated with the early interruption of exclusive BF in the studies evaluated. Its use may imply a decrease in the frequency of sucking, resulting in less stimulation of the nipple-areolar complex and consequent reduction in the production of breast milk.…”
Section: Discussionmentioning
confidence: 98%
“… 1 , 12 , 13 The pacifier habit is a predictive factor for the interruption of exclusive BF, since it can reduce the frequency with which the child sucks on the breast, reducing the production of breast milk and changing the infant’s oral dynamics, which reinforces the orientation that the mothers should not offer it to the newborn; 6 however, studies are still controversial. 6 , 14 , 15 , 16 The number of children is another relevant aspect, since it is closely related to previous experiences with breastfeeding. There is an increase in the prevalence of exclusive BF among mothers who have breastfed, correlating with their previous experiences.…”
Section: Introductionmentioning
confidence: 99%
“…From these three studies, only one investigated myofunctional orofacial aspects, in addition to the occlusal conditions, and an evaluation was conducted by a single audiologist, collecting qualitative data (31) . The use of equipment for quantitative measurements should be considered, as well as the addition of investigations on orofacial functions, in order to link the execution of harmful habits with early weaning (interference in the nutritive sucking function) as an example (12,13) . Regarding the methodological rigor, it was observed that a study conducted the calibration of examiners and intra-and interexaminers validation (30) , while the other two studies conducted to data collection through one examiner, who was blind about the history of pacifier-sucking habit (31,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Literature agrees that breastfeeding for a long time is related to a lower incidence of non-nutritive sucking habits (10,11) . Thus, the use of bottles and pacifiers may result in the interruption of breastfeeding (12,13) or in it becoming complementary and non-exclusive (12) . Harmful oral habits, such as thumb sucking or the use of pacifiers and bottles, are learned and often repeated patterns of muscle contraction (14) and may cause damage to the morphophysiology of the stomatognathic system (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%